1984
DOI: 10.1104/pp.76.1.244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Stress on Photosynthesis and Carbon Partitioning in Soybean (Glycine max [L.] Merr.) Plants Grown in the Field at Different CO2 Levels

Abstract: The effects of water stress and CO2 enrichment on photosynthesis, assimilate export, and sucrose-P synthase activity were examined in field grown soybean plants. In general, leaves of plants grown in C02-enriched atmospheres (300 microliters per liter above unenriched control, which was 349 ± 12 microliters per liter between 0500 and 1900 hours EST over the entire season) had higher carbon exchange rates (CER) weight accumulation of leaves during the light period (28), provides an estimate of the rate of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
2
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(67 citation statements)
references
References 24 publications
9
55
2
1
Order By: Relevance
“…Productivity and stomatal conductance in the field-grown ore wheats decreased with a resultant reduction in transpiration and total water loss. Our results are in good agreement with those from other field studies in different environments (Huber et al 1984;Idso et al 1987;Lawlor and Mitchell 1991).…”
Section: Discussionsupporting
confidence: 83%
“…Productivity and stomatal conductance in the field-grown ore wheats decreased with a resultant reduction in transpiration and total water loss. Our results are in good agreement with those from other field studies in different environments (Huber et al 1984;Idso et al 1987;Lawlor and Mitchell 1991).…”
Section: Discussionsupporting
confidence: 83%
“…However, the observed reduction of Ai in plants submitted to water deficit was attributed to a decrease in Y L (Figures 2a,b; 6a,b), as reported by other authors (Bunce 1982;Egli and Bruening, 2004;Liu et al 2004a,b;Ribas-Carbo et al 2005). It is known that low Y L increases the stomatal resistance, which in turn reduces the CO 2 uptake, thereby affecting leaf photosynthesis by the diffusive process (Huber et al 1984). Therefore, the low grain-yield found in T2 and T3 plants can be attributed to the photosynthesis reduction per unit of leaf area and photosynthesis on the canopy scale in response to the LA reduction (Figures 3b,e; 6a,b).…”
Section: Effects Of Water Deficit On Photosynthetic Productionsupporting
confidence: 55%
“…This shows that the response of leaf weight was relatively higher than the expansion of the leaves and thereby leaves are thicker under elevated CO 2 . Huber et al (1984) concluded that the increase in specific leaf mass (leaf weight/leaf area) was presumably due mostly to the increase in starch content but the leaves of soybean are also thicker under enhanced CO 2 condition, due to the increase in palisade cells, which was not observed in maize (Thomas andHarvey 1983, Lawlor andMitchell 1991).…”
Section: Resultsmentioning
confidence: 99%